Neurophysiological correlates of emotional face perception consciousness. (September 2020) - Lai, Carlo; Pellicano, Gaia Romana; Ciacchella, Chiara; Guidobaldi, Lorenzo; Altavilla, Daniela; Cecchini, Marco; Begotaraj, Edvaldo; Aceto, Paola; Luciani, Massimiliano
Abstract: Aim of the present study was to investigate the neurophysiologic correlates of the conscious and not conscious perception of faces (presented for 14, 40, 80 ms) with happy and sad emotional valence. Electroencephalographic data of 22 participants during a report-based visual task were recorded. Both happy and sad faces presented for 14 ms showed a longer N170 latency compared to the faces presented for 40 and 80 ms. A shorter latency of early components (before N170) was found in the right hemisphere and a longer latency in the left one in response to the happy faces presented for 14 ms compared to those presented for longer times. The faces presented for 14 ms, declared as consciously perceived, evoked a higher brain response compared to those declared as not perceived. Parietal and cingulate brain areas showed a lower intensity of the brain response to the consciously perceived faces in the early components. Happy faces showed a greater brain response when consciously detected, while the sad faces induced a greater brain response when not consciously detected. The findings suggest that the N170 may be the epiphenomenon of an earlier consciously detection. Moreover, these preliminary results seem to support a main role of parietal and cingulate brain areas into not conscious perception. Highlights: Brain response to conscious and not conscious perceived faces were investigated. Consciously perceived faces elicited a higher activity mainly in parietal ROI. Happy faces vs. sad ones evoked a different brain response even if not conscious.